2021
DOI: 10.3390/agriculture11040317
|View full text |Cite
|
Sign up to set email alerts
|

Irrigation Post-Modernization. Farmers Envisioning Irrigation Policy in the Region of Valencia (Spain)

Abstract: During the last three decades, like many other Mediterranean states, Spain has intensively promoted the modernization of irrigation, focusing mainly on the introduction of pressurized irrigation systems. Following 30 years of investment, a shift in irrigation policies is needed to solve some of the deficiencies in this modernization process and to incorporate new measures to cope with upcoming challenges generated by international markets, climate change and other social and economic processes. This paper desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…This means that the financial viability of water reuse is affected in the context of rising energy prices [26]. This energy problem is also perceived by irrigators, the main users of reclaimed water in Spain, as it not only means an increase in the price of water but also requires available energy to carry out this activity [48]. For this reason, the use of renewable energy sources has become a topical issue in water services, as they can provide both financial and environmental benefits [48][49][50].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This means that the financial viability of water reuse is affected in the context of rising energy prices [26]. This energy problem is also perceived by irrigators, the main users of reclaimed water in Spain, as it not only means an increase in the price of water but also requires available energy to carry out this activity [48]. For this reason, the use of renewable energy sources has become a topical issue in water services, as they can provide both financial and environmental benefits [48][49][50].…”
Section: Introductionmentioning
confidence: 99%
“…This energy problem is also perceived by irrigators, the main users of reclaimed water in Spain, as it not only means an increase in the price of water but also requires available energy to carry out this activity [48]. For this reason, the use of renewable energy sources has become a topical issue in water services, as they can provide both financial and environmental benefits [48][49][50]. Finally, the presence of an obsolete infrastructure is also perceived as a major problem by irrigators [48,51,52].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The modernization of irrigation schemes in Spain [2], and also in the Valencia region [3], has entailed changing from open channels networks for surface irrigation to pressurized pipes networks and drip irrigation systems. This modernization has allowed the reduction in irrigation water use [4,5] and improved the control of irrigation application by farmers [2,5] aided by irrigation management and information systems at the national level [6] and at the Valencian Community regional level [7].…”
Section: Introductionmentioning
confidence: 99%
“…Gonçalves et al [ 3 ] conducted an efficiency analysis in the Lis Valley Irrigation District in Portugal and found that the overall efficiency in the district was 67% and concluded that it is important to maintain, conserve and modernize the hydraulic infrastructure. In Spain, for three decades, they have promoted the use of pressurized irrigation systems to reach 72% of the arable area [ 4 ], in Brazil, the main modern irrigation technique is the central pivot irrigation system with a 78.3% of irrigable area [ 5 ].…”
Section: Introductionmentioning
confidence: 99%